Completely blind image quality assessment via contourlet energy statistics - Chaofeng Li; Tuxin Guan; Yuhui Zheng; Bo Jin; Xiaojun Wu; Alan Bovik (IET Image Processing, 2021)
Abstract An aim of completely blind image quality assessment (BIQA) is to develop algorithms which can grade image quality without any prior knowledge of the images. Here, a new contourlet energy statistics based completely on blind opinion‐unaware BIQA (OU‐BIQA) method is proposed, which can predict the perceptual severity of a range of image distortion types without requiring any prior knowledge. According to the energy distribution of the contourlet sub‐bands of natural images in log‐domain, the lower‐scale sub‐band energy can be predicted by the corresponding higher‐scale sub‐band energies of distorted images. A quality model is then constructed by quantifying the difference between predicted energy and realistic energy. Meanwhile, an effective method for adjusting and compensating an undesired distortion is integrated into the quality model. Experimental results show that the proposed new method outperforms state‐of‐the‐art OU‐BIQA models on relevant portions of TID2013 database, and is competitive on the LIVE IQA database. Moreover, the proposed model is very fast, suggesting a real‐time solution to high‐performance BIQA.